Implementasi “The Prosperous Africa Program” Pemerintah Amerika Dalam Bidang Ekonomi Sebagai Upaya Mengatasi Kemiskinan di Nigeria - Sayoga, Ihya Pradnya; Agil Pambudi, Putra; Erlintang, Amelia; Ning Tias, Rahma; Wachid, Choirul (Journal of International Relations on Energy Affairs, 2024)
Nigeria, a country in Africa, is a country that is quite famous for its large economy. However, behind the country's large economy, there is an ongoing problem of poverty. The problem of poverty is caused by several aspects, such as high unemployment and corruption. This also has an impact on community welfare and the emergence of significant societal disparities. Several efforts have been made by the Nigerian government to overcome the country's poverty problem. However, the steps that have been taken are still not enough to stabilize welfare and the disparities that have occurred. To further overcome this problem, the United States launched a program called "The Prosperous Africa Program" in the economic sector to help Nigeria overcome poverty in her country. This article will discuss the implementation of the American Government's "The Prosperous Africa Program" in the economic sector as an effort to overcome poverty in Nigeria. The analysis of this paper will use descriptive qualitative research methods and the theoretical framework of Foreign Aid.